Leadershift the 11 essential changes every leader must embrace - Maxwell, John C. 1947- (HarperCollins Leadership, 2019)
Internationally recognized leadership expert John C. Maxwell teaches listeners how to shift leadership to keep innovating, improving, and influencing others in today's fast-paced world. Change is so rapid today that leaders must do much more than stay the course to be successful. If they aren't nimble and ready to adapt, they won't survive. The key is to learn how to leadershift. Maxwell helps leaders gain the ability and willingness to make leadership changes that will positively enhance their organizational and personal growth.